Odvzem protipravno pridobljenega premoženja - Varanelli, Luigi (Podjetje in delo, 2013)
Assets of Illicit Origin Forfeiture Act is at the juncture of civil and criminal law. Substantial criminal law is the basis enabling the forfeiture of assets of illicit origin. Namely, the term illicit origin is intertwined with substantial criminal law provisions. Civil law is incorporated into criminal law since the concept of assets is a civil law notion. Forfeiture of assets of illicit origin is thus a result of combined application of both of them. The assets subject to forfeiture are composed both by property and rights deriving directly from criminal activity and property and rights deriving only indirectly from criminal activity (interest, etc.). The article especially deals with the question of simulation, since the author anticipates it to be the most contested issue in front of the courts and he offers some possible solutions to the most burning questions concerning simulation.
Keywords: kazniva dejanja; pravna ureditev; premoženje; zaplemba premoženja